Consumer Preference on Demand for Avocado in Traditional Markets Aceh Utara District - Puarada, Sakral Hasby; Sari, Cut Rozana; Yanto, Nopri; Nugrahawati, Anis (PT FORMOSA CENDEKIA GLOBAL, 2023)
Consumer demand is an action taken by consumers to buy a product. The first objective of this study was to analyze and determine the effect of income, education, number of dependents, and the price of avocado on the demand for avocado butter in the traditional markets of North Aceh District. The second objective is to analyze the order of attributes of the most important mango avocado fruit according to consumer preferences in traditional markets in North Aceh District. This study was tested with validity and reliability tests and analyzed using multiple linear analysis and obtained the calculated F results from both traditional markets to obtain significant results so that reject Ho and accept H1 means simultaneously (simultaneously) with a 95% confidence level.